Geomorfologi Daerah Bajo dan Sekitarnya, Kecamatan Tilamuta, Kabupaten Gorontalo - Hemu, Alit Anastasya; Arifin, Yayu Indriati; Raharjo, Purnomo (-, 2025)
This study aims to analyze the geomorphological conditions of Bajo Village and its surroundings, Tilamuta District, Boalemo Regency. The methods used include slope analysis, river flow patterns, and geomorphological units. The data employed consist of topographic maps, satellite images, and the National Digital Elevation Model (DEMNAS), processed using ArcGIS software. Slope analysis was conducted to determine the steepness of the land, while river flow patterns were classified according to Howard (1967). Determination of geomorphological units was carried out through the interpretation of morphology and lithology, referring to Van Zuidam (1983). The results show four geomorphological units, namely fluvial lowlands, marine lowlands, low structural hills, and inland volcanic lowlands. The study area has slopes ranging from flat to steep, with rectangular river flow patterns dominant in the northeastern part. Overall, the geomorphological conditions of this area are influenced by lithology, geological structures, and fluvial processes that actively shape the local morphology.